Social Networking: New Challenges in the Modern Workplace - Muñoz Ruiz, Ana Belén (SPANISH LABOUR LAW AND EMPLOYMENT RELATIONS JOURNAL, 2013)
The past few years have witnessed an exponential growth in the use of social networking. Employees often share photos, write messages to friends or leave virtual ‘gifts’, which are sometimes related to their employment. Indeed, employers sometimes use information found on these sites to make pre-employment decisions or take disciplinary action. In this paper we wish to focus our attention on Spanish case law and to contrast the criteria employed in this law with that of other relevant countries such as Germany, France or the United Kingdom. The overall purpose of this article is to rethink the scope of labour law and to examine how industrial relations are affected by employee’s personal conduct.